Effects of vitamin C on oxidative stress induced endothelial dysfunction in rapid eye movement (REM) sleep deprivation rat model - Tengku Adnan, Tengku Farah Adilah (2018)
Sleep deprivation has been identified as a risk factor for cardiovascular disease. Endothelial dysfunction is an early sign of cardiovascular disease. To date, the pathogenesis of endothelial dysfunction in sleep deprivation remains poorly understood. The objectives of this study were to assess the relationship between sleep deprivation in particular REM sleep phase, and endothelial dysfunction. The effects of vitamin C on the adverse effects of REM sleep deprivation were also evaluated. Forty (40) male Sprague–Dawley (SD) rats were equally divided into 5 groups: freemoving control rats (FMC), 72-h REM sleep-deprived rats (REMsd), REMsd pretreated with vitamin C (RVC), FMC pretreated with vitamin C (FVC) and tank control rats (TC). Rats were deprived of REM sleep using the inverted flowerpot technique. Vitamin C (100 mg/kg) was administered orally for 4 weeks before the adaptation period. There was a significant reduction of body weight gain despite a significant increase in food consumption in REMsd compared to FMC group. In in vitro functional study, REMsd group showed the lowest endothelium-dependent vasodilator responses to acetylcholine (ACh) compared to other groups. eNOS expression determined by Western blot was significantly lower in REMsd compared to FMC group. Glutathione reductase (GR) and superoxide dismutase (SOD) activities, and total antioxidant capacity (TAC) were significantly lower in REMsd compared to FMC group. The plasma levels of malondialdehyde (MDA) were not significantly different between the groups. A significant increase in plasma levels of fibrinogen and plasminogen activator inhibitor-1 (PAI-1), and decreased tissue plasminogen activator (tPA) level were observed in REMsd compared to FMC, which indicate an activation of coagulation cascade in REMsd group. The endothelium morphology is normal in all groups when assessed by hematoxylin and eosin staining. However, in scanning electron microscope, the endothelium of REMsd rat only showed features of endothelial damage. Vitamin C reduced the adverse effects of REM sleep deprivation by preserving the endothelial function, restoring the eNOS expression, increasing the SOD activity and protecting the endothelium from damage. Vitamin C also helps in preventing the reduction of GR activity and TAC, and changes to the coagulation factors during REM sleep deprivation. In conclusion, the above findings provide convincing evidence for the development of endothelial dysfunction in REM sleep deprivation. Supplementation of vitamin C has beneficial effects against oxidative stress induced endothelial dysfunction in REM sleep deprivation.